Migration, trapping, and venting of gas in a soft granular material - Lee, S; Lee, J; Le Mestre, R; Xu, F; MacMinn, CW (American Physical Society, 2020)
Gas migration through a soft granular material involves a strong coupling between the motion of the gas and the deformation of the material. This process is relevant to a variety of natural phenomena, such as gas venting from sediments and gas exsolution from magma. Here, we study this process experimentally by injecting air into a quasi-2D packing of soft particles and measuring the morphology of the air as it invades and then rises due to buoyancy. We systematically increase the confining prestress in the packing by compressing it with a fluid-permeable piston, leading to a gradual transition in migration regime from fluidization to pathway opening to pore invasion. We find that mixed migration regimes emerge at intermediate confinement due to the spontaneous formation of a compaction layer at the top of the flow cell. By connecting these migration mechanisms with macroscopic invasion, trapping, and venting, we show that mixed regimes enable a sharp increase in the average amount of gas trapped within the packing, as well as much larger venting events. Our results suggest that the relationship between invasion, trapping, and venting could be controlled by modulating the confining stress.